Determinants of length for age Z scores among children aged 6–23 months in Central Java, Indonesia: a path analysis - Kartasurya, Martha Irene; Syauqy, Ahmad; Suyatno, Suyatno; Dewantiningrum, Julian; Nuryanto, Nuryanto; Sunarto, Sunarto; Isnawati, Muflihah; Nurcahyani, Yusi Dwi; Wati, Erna Kusuma; Hapsari, Pramesthi Widya; Samsudin, Mohamad; Fuada, Noviati (Frontiers in Nutrition, 2023)
Length for Age Z (LAZ) scores determinants are complex and vary among different areas, but it is important for designing effective and efficient strategies to decrease stunting prevalence among under two children. This study aimed to investigate the determinants of LAZ scores among under-two children in Central Java, Indonesia. This study was conducted on 2021 INSS (Indonesian Nutritional Status Study) data set, which was a cross sectional survey. Data on 3,430 children aged 6–23 months from Central Java Province were derived from 2021 INSS data. After missing data elimination, 3,238 subjects were included in the analysis. Determinant factors included direct and indirect factors. Direct factors were mother’s age, birth weight Z score (BWZ), birth length Z score (BLZ), exclusively breastfed history, Dietary Diversity Scores (DDS), empty calorie drink consumption, unhealthy snacks consumption and infections. Indirect factors were Early Initiation of Breastfeeding (EIBF), posyandu (integrated health post) utilization. Underlying factors were socioeconomic status (SES) and mother’s education. Bivariate analyses and multiple linear regressions were conducted. A path analysis with a hypothesized model based on UNICEF conceptual framework was also performed. The results showed that the stunting proportion among the subjects was 19.1%, wasting 7.6% and underweight 12.3%. The mean LAZ scores were -0.95 ± 1.22, mother’s age 29.7 ± 5.95 years, BWZ -0.47±0.97, BLZ -0.55±1.05, DDS 4.45±1.51. The infection proportion among the subjects was 28%. BWZ and BLZ were positively correlated to LAZ scores, with r= 0.267 (p<0.01) and r=0.260 (p<0.01), respectively. Mother’s age was negatively correlated to LAZ scores with r= -0.041 (p<0.05) . Maternal education positively correlated to the SES, but had no direct effect on LAZ scores. LAZ scores determinants of BLZ (p<0.001) and SES (p<0.001) showed positive direct associations with LAZ scores, but mother’s age (p=0.039), exclusively breastfed history (p<0.001), empty calorie drinks consumption (p<0.001) had negative associations with LAZ scores. To prevent stunting among children aged 6-23 months in Central Java, Indonesia, intervention programs to increase the nutritional status of women at child bearing age as well as nutrition education on child feeding practices should be conducted more efficiently and effectively.